EMPLOYMENT OF UKRAINE'S POPULATION IN THE CONTEXT OF PROTECTION OF ITS LABOR POTENTIAL (Regional aspects of productive forces development of Ukraine, 2019)
The article deals with the issues of employment of economically active population. For the period 2011–2017 the dynamics of the number of employed population is analyzed. The current trends in employment in the countries of the European Union are odserved. The reasons for reducing the number of employed are found. The quantitative parameters of labor potential of Ukraine are calculated as well as the features of regional employment are analyzed.